The Effect of Sport Vision Training on Quiet Eye Period and Accuracy of Targeting-Interceptive Skill in Children with Learning Disorder ‎ - Nayereh Shamshiri; Zohreh Meshkati; Rokhsareh Badami (University of Tehran, 2022)
Introduction and Purpose: the purpose of this study was to examine the effect of sport vision training on accuracy and targeting-interceptive skill quiet eye in children with learning disorder.Methods: In this semi- experimental study with a repeated-measure design, 30 boys aged 7-10 years with learning disorder were divided into sport vision and control groups. In the pre-test phase, participants performed 10 trails to throw and catch task the ball. Acquisition phase have done in eight weeks and three sessions in per weeks. At the end of the last training session, in the post-test phase, in two weeks of detraining in the retention and transfer phases, the participants performed 10 trials to throw and catch task the ball. At each phase, the gaze behavior was recorded by eye tracker system and the throw and catch task performance was recorded by the researcher. Data were analyzed by analysis of variance with repeated measures with 0.05 significant levels.Results: The results indicated that sport vision training has a significant effect on increasing the accuracy of targeting-interceptive skills and on increase quiet eye period of throw phase. But, other result indicated that sport vision training has not effect on quiet eye of catching phase.Conclusion: In general, the results of the current study emphasize the importance of sports vision training on the performance of children with learning disabilities; However, more research is needed on the effect of sports vision training on gaze behavior according to the type of task (targeting or interceptive).